Graphitic carbon nitrides as electrode supporting materials for lithium-ion batteries: what lies ahead in view of the current challenges? - Sajid, Mohd; Chandio, Zubair Ahmed; Hwang, Byungil; Yun, Tae Gwang; Cheong, Jun Young (Frontiers in Energy Research, 2023)
Graphitic carbon nitride (g-C3N4) has emerged as a promising material for various applications, particularly in the field of energy storage systems. Among these systems, lithium-ion batteries (LIBs) have become the cornerstone of portable electronics and are increasingly being adopted for electric vehicles and renewable energy storage. However, the search for alternative electrode materials that can overcome the limitations of traditional graphite anodes and transition metal oxide cathodes remains a significant challenge. In recent years, g-C3N4 has attracted considerable attention due to its unique physicochemical properties, such as high electrochemical stability, tunable bandgap, large specific surface area, and excellent thermal and chemical stability. Also, the low cost, abundance, and environmental sustainability of g-C3N4 contribute to its suitability for next-generation LIBs. However, the successful utilization of g-C3N4 as an electrode material is hindered by several challenges. This paper aims to explore the challenges and future perspectives of utilizing g-C3N4 as a potential electrode material for LIBs, highlighting the potential benefits and drawbacks of integrating this material into the battery system.
Keywords: current; Electrode material; Graphitic; Graphitic carbon nitrides; Portable electronics; Rechargeable; Renewable energy storages; Storage systems; Supporting material; Vehicle energy; carbon nitride; electrode; graphitic; lithium; rechargeable